The Influence of Emotional Regulation on Tendencies Suicide In Early Adulthood In East Jakarta - Putri, Tanya Septiani (Asosiasi Asesmen Pendidikan (AAP), 2024)
This research aims to determine the influence of emotional regulation on suicidal tendencies in young adults in East Jakarta. Early adulthood as a period of self-realization, becoming parents, resolving conflicts and emotional tension, social isolation, attachment and dependency, shifting values, creativity, and adopting new ways of living. Adulthood in particular is a period of growth rapidly, but also a time full of conflict. According to Lumen Learning, conflict and crisis in early adulthood can take the form of feelings burdened with new responsibilities, worries about the future, and division of time between oneself and peers. People who experience difficulty regulating negative or suggestive emotional responses inappropriate emotional responses to certain situations Glatz and Roemer, and unable to recognize, control, and adapt with signs of emotional regulation difficulties. Emotional dysregulation resulting in difficulty controlling maladaptive emotions and behavior or behavior that causes an individual Difficulty in self-regulation is one of the contributing factors physical violence. Emotion regulation is the ability to manage, identify and manage emotions effectively. This involves self-awareness of emotions, an understanding of the factors that trigger emotions, and the skills to manage emotional responses in healthy and productive ways. This research is a quantitative research with research subjects as many as 196 early adults in East Jakarta. Data collection in this study used the Emotion Regulation (ERQ) Questionnaire and Scale for Suicide Ideation measuring instruments. This research uses a simple linear regression data analysis technique to determine the influence of the two variables and is processed using SPSS version 26. Based on the results of data analysis, an F value of 925.630 is obtained with a significance of 0.000 and a coefficient of determination (R2) of 0.838, which shows that emotional regulation has an effect on trend. suicide was 83.8%.